Analysis of Commercial Agriculture Credit Scheme on Profitability of Rice Farming in Kano State, Nigeria: Strategy for Industrial Growth - Gyong, Yerima Emmanuel; Ahmed, Aliyu Tanko (NIU Journal of Social Sciences; Vol 10 No 1 (2024): NIU Journal of Social Sciences, Vol. 10 No. 1, March 2024, 2024)
Commercial agriculture credit scheme (CACS) is one of the Federal Government programs to encourage commercial agriculture. Commercial rice farming is one of those agricultural activities that the Federal Government is promoting.  In Nigeria rice farming is characterized by low productivity and low yield leading to rice shortage. The shortage in production creates the demand and supply gap. This study investigated how the CACS has promoted commercial rice farming in Kano State. Primary data was sourced from 394 beneficiary farmers of CACS through survey method. These rice farmers were sampled from three agricultural zones in Kano; Zone I (Rano), Zone II (Danbatta) and Zone III (Gaya). The study employed the gross margin analysis, techniques of analysis.  The Gross Margin Analysis revealed before CACS that total revenue generated from sales ₦26,359,950.00 and the total variable cost was ₦410,282.36. After CACS was ₦122,893,500.00 and the total variable cost was ₦8,001,970.73. The average rate of returns on investment (Return per Naira Invested) was ₦63.24 before CACS and ₦14.35 per planting period. Government should have a standard policy measure to promote domestic rice product to make it marketable and more profitable. For instance, the policy of branding and packaging by engaging farmers directly. The profitability analysis reveals that if more increased loan is giving to farmers to access the loan, there will be increase in profitability of rice farming and this can lead to growth of the rice industry. Keywords: Commercial Agricultural Credit Scheme, Production, Farming, Profitability, Gross margin, Industrial Growth